Investigating the Effectiveness of Brexpiprazole in Subjects with Schizophrenia Spectrum Illness and Co-Occurring Substance Use Disorder: A Prospective, Multicentric, Real-World Study - Stefania Chiappini; Clara Cavallotto; Alessio Mosca; Francesco Di Carlo; Tommaso Piro; Giulia Giovannetti; Arianna Pasino; Mariachiara Vicinelli; Chiara Lorenzini; Mariapia Di Paolo; Maria Pepe; Marco Di Nicola; et al. (MDPI AG, 2024)
Background: Dual disorders (DDs) involve the coexistence of a substance use disorder (SUD) with another mental illness, often from the psychotic and affective categories. They are quite common in clinical practice and present significant challenges for both diagnosis and treatment. This study explores the effectiveness of brexpiprazole, a third-generation antipsychotic, in an Italian sample of individuals diagnosed with schizophrenia spectrum disorder and a comorbid SUD. Methods: Twenty-four patients, diagnosed according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and enrolled in several Italian hospitals, underwent a psychometric assessment at baseline (T0) and one month (T1) after starting brexpiprazole treatment administered at a mean dosage of 2 mg/day. Results: Brexpiprazole demonstrated significant reductions in psychopathological burden (Positive and Negative Syndrome Scale/PANSS total score: p < 0.001). Positive (p = 0.003) and negative (p = 0.028) symptoms, substance cravings (VAS craving: p = 0.039), and aggression (MOAS scale: p = 0.003) were notably reduced. Quality of life improved according to the 36-item Short Form Health Survey (SF-36) subscales (p < 0.005). Conclusions: This study provides initial evidence supporting brexpiprazole's efficacy and safety in this complex patient population, with positive effects not only on psychopathology and quality of life, but also on cravings. Further studies involving larger cohorts of subjects and extended follow-up periods are needed.